2020
DOI: 10.1371/journal.pone.0222126
|View full text |Cite
|
Sign up to set email alerts
|

Application of non-invasive low-intensity pulsed electric field with thermal cycling-hyperthermia for synergistically enhanced anticancer effect of chlorogenic acid on PANC-1 cells

Abstract: Most existing cancer treatments involve high-cost chemotherapy and radiotherapy, with major side effects, prompting effort to develop alternative treatment modalities. It was reported that the combination of thermal-cycling hyperthermia (TC-HT) and phenolic compound exhibited a moderate cytotoxic effect against human pancreatic cancer PANC-1 cells. In this study, we investigate the efficacy of triple combination in PANC-1 cancer cells by adopting low-intensity pulsed electric field (LIPEF) to couple with TC-HT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Recently, mutant p53 has become an attractive target for cancer therapy (45). Reportedly, it also induces apoptosis through activation of mutant p53 (46)(47)(48). 3EZ, 20Ac-ingenol also significantly increased the expression of mutant p53 protein and the p53-downstream target gene p21 and the activation of caspase 3 in Panc-1 cells.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, mutant p53 has become an attractive target for cancer therapy (45). Reportedly, it also induces apoptosis through activation of mutant p53 (46)(47)(48). 3EZ, 20Ac-ingenol also significantly increased the expression of mutant p53 protein and the p53-downstream target gene p21 and the activation of caspase 3 in Panc-1 cells.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, it is believed that the development of non-contact, non-invasive electric field therapy will be inevitable, which can also be further applied in conjunction with drugs for various therapeutic purposes. Previously, our team has achieved synergistic inhibitory effects on cancer cells by combining such electric fields with herbal extracts such as EGCG, CGA, and curcumin, and has also accomplished satisfactory results in repairing mouse motor neuron cell NSC-34, demonstrating the versatility of non-contact, non-invasive electric field stimulations [Hsieh et al, 2017; Hsieh et al, 2018; Lu et al, 2018; Hsieh et al, 2019 Lu et al, 2020]. In application, the electric field’s strength and frequency would vary among different cellular tissues, depending on accompanying drugs, tissue structure, and protein response, which needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…Third, ultrasound can be added to the combination treatment, further boosting the anticancer effect [Hsieh et al, 2018]. Moreover, our team has found another effective anticancer triple therapy, combining LIPEF, chlorogenic acid (CGA), and thermal cycling-hyperthermia technique [Lu et al, 2020]. Besides, LIPEF can join hands with fucoidan to modulate rho-associated protein kinase (ROCK) and the downstream Akt protein, thereby protecting motor neurons NSC-34 against damage by oxidative stress [Hsieh et al, 2019].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also reported a decrease in cell viability and increased DNA fragmentation and ROS production [37,38]. The combination therapy induced the mitochondrial activation and increased the Caspases-9, -3 and poly ADP-ribose polymerase (PARP) expression leading to apoptosis [39]. In one study, authors showed that hyperthermia increased e cacy of PDT on gastric cancer cells through elevated ROS production leading to enhanced PDT-induced cytotoxicity [37].…”
Section: Discussionmentioning
confidence: 99%